2018
DOI: 10.26717/bjstr.2018.04.0001125
|View full text |Cite
|
Sign up to set email alerts
|

“Emerging Trends of Herbs and Spices in Dentistry”

Abstract: Cloves offer many health benefits, some of which include aiding in digestion, fighting against cancer, protecting the liver, boost-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…However, in vivo toxicity studies and clinical trials are still necessary. The studies carried out in recent decades have confirmed the anti-caries role of probiotics and natural compounds extracted from herbs and spices [75]. Their main action is based in three effects: reduce bacterial growth rate, reduce the adhesion ability of pathogens, and inhibit the enzymatic activity of glucosyltransferase and amylase [72,73,88].…”
Section: Incorporation Of Natural Antimicrobials In Cariesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in vivo toxicity studies and clinical trials are still necessary. The studies carried out in recent decades have confirmed the anti-caries role of probiotics and natural compounds extracted from herbs and spices [75]. Their main action is based in three effects: reduce bacterial growth rate, reduce the adhesion ability of pathogens, and inhibit the enzymatic activity of glucosyltransferase and amylase [72,73,88].…”
Section: Incorporation Of Natural Antimicrobials In Cariesmentioning
confidence: 93%
“…It is necessary to investigate plant extracts, which contain many different bioactive compounds. Researches have indicated that cinnamon, clove, and coriander are effective in preventing dental caries [75]. The antimicrobial activity of phenolic acids is related to the number and position of substituents on the benzene ring.…”
Section: Plant-derived Cariogenic Biofilm Inhibitorsmentioning
confidence: 99%
“…Ayurveda is one of the systems of traditional medicine that employs the use of medicinal plants in treating various diseases [1]. Tulsi is also known as "Holy Basil," and in Sanskrit it was mentioned as `the incomparable one," and it was referred to as the `Queen of Herbs ` [2,5].…”
Section: Historical Background Of Tulsi :-mentioning
confidence: 99%
“…God has created medicinal marketers in the name of herbs for human beings. The understanding of medicinal plants has been gathered over many centuries [1]. Many medicinal plants have gained importance in the field of dentistry [2].…”
Section: Introduction :-mentioning
confidence: 99%
“…When considering the effect of turmeric on nervous system, curcumin and manganese complex may provide protectio against vascular dementia by deploying the antioxidant activity (Thiyagarajan and Sharma, 2004). Further, turmeric acts as an excellent scavenger of free radicals by increasing the number of micronuclei in the circulating lymphocytes (Sachdeva et al, 2018).…”
Section: Antioxidant Activitymentioning
confidence: 99%